Emotional Intelligence: Source of Self-Efficacy Among College-Level Instructors of Pakistan - Anjum Bano Kazmi; Ume-Nabeela Siddiqui; Sohni Siddiqui (Performance Improvement, 2021)
Perceived importance of emotional intelligence has increased significantly in the past few decades; thus, it is suggested for everyone to acquire adequate skills beyond theoretical or mechanical knowledge and make themselves emotionally fit and stable. The study is designed to provide an explanation for the shared results of teacher's self-efficacy and their emotional intelligence. Two hundred and sixty-four (101 males, 163 female) instructors from public colleges situated in Karachi, Pakistan, were selected through random sampling. Data gathered through emotional intelligence scale adapted from Daniel Goleman model of emotional scale and Bandura's instrument of teachers' self-efficacy. Hypothesis testing achieved through regression analysis using SPSS version 20 suggested that emotional intelligence directly and significantly affects self-efficacy. In addition, age and years of experience of participants in particular field have indicated significant impact on emotional intelligence but self-efficacy is influenced only by age, not by experience. It is also concluded from hypothesis testing that there is no association of emotional intelligence and self-efficacy with gender of participants. It is suggested that amateur teachers' self-efficacy can be advanced through professional training, especially related to emotional intelligence.
Keywords: 300